Cognition and Behavior of Oral Health in Preschool Parents. (Medico Legal Update, 2020)
Background/Objectives: This study was conducted to investigate the oral health cognition and behavior of 83 children’s parents. The results of this study were as follow. First, the questionnaire consisted of eight items on oral health behavior and three items on parental oral health cognition. Improper oral health care behavior responses resulted, and the necessity of fluoride application of oral health awareness scored lower than the necessity of oral health education and regular dental checkups.Method/Statistical Analysis: Targeting a total 83 parents at daycare centers in the C region, September 2018-October 2018, this study distributed the home notification, questionnaire, and research consent form to each home through their children. The completed research consent forms and questionnaires were collected by the daycare centers from the children.Findings: The three times of brushing daily, two-three minutes of brushing each time, and the ‘1/3, 1/2 of the toothbrush for the amount of toothpaste used received the most responses. Many respondents changed their toothbrushes every four weeks. 72.3% of respondents used fluoride toothpaste, and 72.3% of respondents were controlling food and snacks containing sugar. 73.5% of parents were receiving regular oral examination, and 30.0% of parents received it once a year. 84.3% of parents were using secondary oral hygiene products. The average oral health perception was 4.26 while the necessities of fluoride application, regular dental examination, and oral health education averaged 3.59, 4.63, and 4.63 respectively.Improvements/Applications: It would be necessary to vitalize the oral health project and oral health education for parents and children, and also to have accurate and systematic studies on more inclusive and diverse elements.